Extraparotid Warthin Tumors Imitating Metastasis of Oral Cancers - Gontarz, Michał; Gąsiorowski, Krzysztof; Bargiel, Jakub; Marecik, Tomasz; Szczurowski, Paweł; Zapała, Jan; Wyszyńska-Pawelec, Grażyna (International Archives of Otorhinolaryngology, 2021)
Introduction Extraparotid Warthin tumor (WT) is a very rare entity, especially when synchronous with oral cancer (OC).Objective The present study presents a case series of extraparotid WTs detected in the surgical specimen of patients treated for OC.Methods From 2007 to 2016, 336 patients were operated for OC in our institution. Neck dissection was performed in 306 patients.Results In the 306 patients operated for OC whose necks were dissected, unexpected WTs were observed in 4 surgical neck specimens. In 3 cases, extraparotid WTs were responsible for tumor, node, metastasis (TNM) overstaging before surgery.Conclusion Extraparotid WTs may be discovered during neck dissection in ∼ 1% of OC patients, and they may mimic neck metastasis, especially in positron-emission tomography/computed tomography (PET/CT) imaging.
Keywords: Warthin tumor; adenolymphoma; squamous cell carcinoma; mouth neoplasms; head and neck squamous cell carcinoma